2015
DOI: 10.1387/ijdb.150200jh
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma and calcium signaling - analysis of calcium toolbox expression

Abstract: The characteristics of a cellular calcium signal (calcium signature) are determined, at least partly, by the expression of a subset of genes encoding proteins involved in calcium entry, calcium uptake and calcium modulation. Our aim in the present work was to characterize the set of genes involved in calcium signal generation that are differentially expressed in normal brain tissues versus brain tumor and/or glioma stem cells. Public datasets were analyzed according to a four step methodology consisting of: 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…A similar analysis has been recently carried out in glioblastoma using data gathered from repository data sets of a large series of glioblastomas [23]. Data shown here were generated using Ion Torrent RNA-sequencing from mRNA isolated from normal human colonic NCM460 cells and colon cancer HT29 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar analysis has been recently carried out in glioblastoma using data gathered from repository data sets of a large series of glioblastomas [23]. Data shown here were generated using Ion Torrent RNA-sequencing from mRNA isolated from normal human colonic NCM460 cells and colon cancer HT29 cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, Ca 2+ remodeling is complex and may involve changes in expression and/or activity of hundreds of genes related to Ca 2+ signaling [23], with nearly 80 of them directly involved in Ca 2+ transport across biological membranes. By taking advantage of Next Generation Sequencing technologies, particularly RNA-sequencing (RNA-seq) by Ion Torrent methodologies, we were able to study in detail intracellular Ca 2+ homeostasis in NCM460 cells reflecting normal human colonic cells [24,25] and HT29 cells [26] representing human colorectal cancer cells, to investigate, for the first time, the transcriptomics of Ca 2+ remodeling in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…This study highlights the importance of calcium management in radioresistance. Interestingly, a large genomic analysis study demonstrated that GSCs have elevated expression of several key genes related to calcium transport, calcium reuptake, and calcium-responding proteins(68); these results suggest that GSCs may have the ability to resist radiotherapy by more efficient calcium management. Given the importance of calcium levels in radiation induced apoptosis, this theory seems like a promising avenue for further investigation.…”
Section: Calcium Management—an Emerging Influence In Radioresistancementioning
confidence: 99%
“…Among the voltagegated ion channels in the brain, calcium channels are especially important as calcium influx plays a pivotal role in cellular signaling 21,22 . Calcium signaling is also important in glioma cell proliferation, resistance to therapy, and metastasis [23][24][25][26][27] . Whether or not the calcium signaling in glioma is mediated by electric field is still an open question.…”
Section: Introductionmentioning
confidence: 99%